2005
DOI: 10.1007/s11089-005-2339-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Geropsychiatric Inpatient Length of Stay

Abstract: Despite efforts to decrease lengths of acute psychiatric hospital stays, some geriatric inpatients continue to have extended stays. This research examined factors related to length of stay (LOS), including legal and administrative factors not traditionally included in prior studies. The charts of 384 patients, representing all 464 discharges from an inpatient geropsychiatric unit over a one-year period, were evaluated retrospectively and analyzed using logistic regression and logarithmic transformation. The LO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 48 publications
3
31
1
Order By: Relevance
“…Some have argued that the impetus to reduce LOS has gone too far, losing sight of the crucial role of the inpatient setting (22). The findings herein, in addition to other research, may be useful for informing staffing decisions, hospital practice planning, and reimbursement negotiations (19); assessing productivity and comparing different hospital settings (23); as well as providing clinicians with information on potential predictors of LOS in acute psychiatric units.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Some have argued that the impetus to reduce LOS has gone too far, losing sight of the crucial role of the inpatient setting (22). The findings herein, in addition to other research, may be useful for informing staffing decisions, hospital practice planning, and reimbursement negotiations (19); assessing productivity and comparing different hospital settings (23); as well as providing clinicians with information on potential predictors of LOS in acute psychiatric units.…”
Section: Discussionmentioning
confidence: 84%
“…Prior analyses with a sample of 221 patients in this dataset indicated that only 36.2% kept their first outpatient community mental health appointment (9). This very low rate of outpatient follow-up adherence, in conjunction with increasing demands to reduce the inpatient LOS, suggests that greater attention must be given to effective discharge planning and bridging strategies (including early planning and attention to disposition, and more inpatient focus on collaboration with families, outpatient clinicians, and social services) designed to avert relapse and rehospitalization (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, if this finding was then taken to the courts, the average treatment delay was 253 days. 13 Incapacity has indirectly been associated with longer hospital LOS on a geriatric psychiatric inpatient unit in a study 14 of 384 patients. Requiring court proceedings to medicate patients against their will increased the probability of having a hospital LOS of 25 days or more (a 10-fold increase from 2.5% to 24.8%) and led to a 65% increase in hospital LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study is the first step to overview the current Korean geropsychiatric inpatient care system, it has several limitations to evaluate such a bundled effect on LOS. First, the national administrative claim databases analysed in this study reflect the entire population of Korea, but it does not include clinical and social information such as severity, onset and duration of illness, recurrence, past medical history, marital status, housing, social support, involuntary admission, and so forth [14,15,42,[66][67][68]. Additionally, only principal diagnoses, not comorbid illnesses, were analysed.…”
Section: Limitationsmentioning
confidence: 99%
“…As a result, the LOS for treating mental disorders has been reduced to an average of 22.0 days in OECD countries, while it is 3.7 days in Norway, 6.9 days in the U.S., and 58.8 days in the U.K. in 2005-2007 [1]. However, few studies have focused on the LOS of geropsychiatric inpatients worldwide and their results are even conflicting [14][15][16][17][18][19]. In addition, it is difficult to apply overseas results to a local situation because each country has its own health care system and culture toward mental illness.…”
Section: Introductionmentioning
confidence: 99%